2020
DOI: 10.3390/medicina56040184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Eleven-Day Altitude Training Program on Aerobic and Anaerobic Performance in Adolescent Runners

Abstract: Background and Objectives: We evaluated the effect of an eleven-day altitude training camp on aerobic and anaerobic fitness in trained adolescent runners. Materials and Methods: Twenty adolescent (14–18 yrs) middle- and long-distance runners (11 males and 9 females; 16.7 ± 0.8 yrs), with at least two years of self-reported consistent run training, participated in this study. Eight of the subjects (4 females/4 males) constituted the control group, whereas twelve subjects (5 females/7 males) took part in a struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…It is also important to note that while the training loads were manipulated differentially between subjects participating in the HRV-guided training group, and in one subject, no training adjustments were made at all. This observation highlights how differently even athletes of a similar skill level may handle a fixed training stimulus and emphasizes the value of individualized training paradigms [ 1 , 3 , 5 , 45 ]. Meanwhile, the members of the control group achieved standard changes in performance [ 32 ].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…It is also important to note that while the training loads were manipulated differentially between subjects participating in the HRV-guided training group, and in one subject, no training adjustments were made at all. This observation highlights how differently even athletes of a similar skill level may handle a fixed training stimulus and emphasizes the value of individualized training paradigms [ 1 , 3 , 5 , 45 ]. Meanwhile, the members of the control group achieved standard changes in performance [ 32 ].…”
Section: Discussionmentioning
confidence: 95%
“…Increases in the HRV and reductions in the HR values throughout an altitude training cycle have previously been observed [ 48 , 49 , 50 ] and are thought to represent acclimatization to the environmental stimulus. In the present study, we similarly observed an upward trend (via visual inspection) in HRV values, beginning on day 9 of the training camp ( Figure 2 ), providing evidence that the training was well-tolerated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This leads to an increase in the number of circulating erythrocytes, suggesting a potential method to rapidly increase the body’s oxygen transport capacity. In contrast, Bahenský et al (2020) tested breathing exercises based on Wim Hof method, which is a combination of deep breathing and breath-holding, increasing the concentration of carbon dioxide in arterial blood and inducing hypercapnia. Induction of hypercapnia prior to exercise is thought to elicit a sympathetic response leading to increased tidal volume (VT) and increased blood flow to skeletal muscle in a manner that may improve exercise performance.…”
Section: Introductionmentioning
confidence: 99%